Pediatric Critical Care Nursing Research Priorities in Asia: An eDelphi Study - Poh, Pei-Fen; Sng, Qian Wen; Latour, Jos M; He, Linxi; Fong, Mei Fung; Muralidharah, Jayashree; Abbas, Qalab; Matsuishi, Yujiro; Lee, Jan Hau (Pediatric critical care medicine, 2022)
To identify nursing research priorities in pediatric critical care in Asia. We conducted a modified three-round eDelphi survey with pediatric critical care nurses in Asia. The eDelphi technique has been extensively used within health research to achieve a common viewpoint from experts using questionnaires to gather research priorities. In round 1, participants were asked to list three to five research topics that they deemed important. These topics were thematically analyzed and categorized into a questionnaire. Participants rated the research topics in round 2 on a 6-point scale (1 = not important to 6 = extremely important). In round 3, the same questionnaire was used with addition of the calculated mean scores from round 2 for each topic. Research topics ranked among the top 10 were considered extremely important. Twenty-two PICUs in eight Asian countries. Clinical nurses, managers, educators, and researchers. None. In round 1, 146 PICU nurses across eight countries provided 520 research topics. Topics from round 1 were categorized into seven domains with 52 research topics. Prioritized research topics included early recognition of patient deterioration (mean 5.58 ± 0.61), prevention of healthcare-associated infections (mean 5.47 ± 0.70), and interventions to reduce compassion fatigue (mean 5.45 ± 0.80). The top three research domains were end-of-life care (mean 5.34 ± 0.68), professionalism (mean 5.34 ± 0.69), and management of pain, sedation, and delirium (5.32 ± 0.72). This first PICU nursing research prioritization exercise within Asia identified key nursing research themes that should be prioritized and provide a framework for future collaborative studies.